Probable Vogt-Koyanagi-Harada’s Syndrome associated with tonic pupils - Narang, S; Sood, S (Nepalese Journal of Ophthalmology, 2010)
Background: Pupillary abnormalities with complete or incomplete form of VKH have rarely been reported. We report a case of "probable" Vogt- Koyanagi-Haradas (VKH) disease associated with tonic pupils. Case: A young healthy male presented with 15 days' history of bilateral decrease in vision. The patient had bilateral panuveitis with exudative retinal detachment associated with tonic pupils. There were no other systemic associations. The ultrasonography and fluorescein angiography findings were consistent with VKH disease. Conclusion: Pupillary reaction abnormalities though uncommon could be seen in association with "probable" VKH disease. Keywords: probable Vogt-Koyanagi-Harada's disease; pupillary abnormalities DOI: 10.3126/nepjoph.v2i2.3723 Nep J Oph 2010;2(2) 154-156